2022
DOI: 10.1007/s11528-022-00805-x
|View full text |Cite
|
Sign up to set email alerts
|

Microlearning through the Lens of Gagne’s Nine Events of Instruction: A Qualitative Study

Abstract: Microlearning provides a valuable and efficient strategy for delivering content to students. As online enrollments continue to increase, further research is needed to determine how students experience microlearning in an online learning format. In this qualitative study, a focus group was used to explore how learners experienced an online microlearning activity through the lens of Robert Gagné’s nine events of instruction. Gagné’s framework is designed to maximize cognitive processing and learner engagement. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…For the implementation and the codebook of Gagne's Nine Events of Instruction, (Rahim et al, 2020) and(McNeill &Fitch, 2023) The application of Gagne's Nine Events of Instruction has benefits and drawbacks. Gagne's Nine Events of Instruction are systematic and simple to apply into teaching and learning process.…”
Section: Table 2 Instructional Events and Cognitive Processmentioning
confidence: 99%
“…For the implementation and the codebook of Gagne's Nine Events of Instruction, (Rahim et al, 2020) and(McNeill &Fitch, 2023) The application of Gagne's Nine Events of Instruction has benefits and drawbacks. Gagne's Nine Events of Instruction are systematic and simple to apply into teaching and learning process.…”
Section: Table 2 Instructional Events and Cognitive Processmentioning
confidence: 99%
“…In a previous study that applied Gagné's class situation, it was said that a wide range of learning activities could be achieved by understanding the concept of learning content for application [34,35]. Moreover, through this process, learners can utilize the learned content at a higher level, leading to an increase in transfer [34][35][36]. This study also helped organize practical training by describing specific questions, related materials, expected learner responses, and time required based on Gagné's nine instructional events.…”
Section: Development Of Nursing Education Using M-learningmentioning
confidence: 99%
“…The implementation of GNEI in synchronous virtual classrooms has been shown to improve several aspects of teaching and learning. Studies have shown that the integration of GNEI into synchronous virtual classrooms increased cognitive processing, student engagement, and overall instructional effectiveness (McNeill & Fitch, 2022). The model's comprehensive framework and adaptability have made it valuable in designing and delivering effective instruction in virtual educational environments.…”
Section: Gagné's Nine Events Of Instructionmentioning
confidence: 99%